(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
In this paper the geometrical characteristics and construction method of hex-tri reciprocal frame are studied. The naming rules of structural units, members and joints of hex-tri reciprocal frame are proposed. Based on the study of relationships between the structural geometrical parameters, the formulas for the joint coordinates of the structural unit are derived, and the calculating method for normalized direction vectors of the unit members is also developed. The geometry construction method of hex-tri reciprocal frame is established in this paper. By this method the whole structure is formed as an assembly of the units arranged in rings about the structural center. The influences of the diameter, the length and the binding length of the member on the rise of hex-tri reciprocal frame are analyzed by an example. If the rise of hex-tri reciprocal frame needs to be specified in the design, the values of the diameter, the length and the binding length of the structural member need to be coordinated to meet the design requirements.